The influence of macroeconomic factors towards housing price in China / Norfarhana Razak - Razak, Norfarhana (2016)
The volatility of housing price can give impacts to developer and consumer's potential profit. There were several effects which are gross domestic product (GDP), interest rate and the inflation rate. It is important to make a research regarding to the relationship between those macroeconomic factors since all all of the factors are related to the volatility of housing price in China. The objective of this study is to identify the relationship between the macroeconomic factors towards housing price in China. The dependent variable use in housing price which determine by housing price index. While for the independent variables there were three; growth rate is determine by GDP, interest rate is determine by base lending rate (BLR) and inflation rate is determine by consumer price index (CPI). This study based on secondary data from the year 1984 until 2014 (30 years) and this research is using Multiple Linear Regressions method in the way of getting the results.